2021
DOI: 10.2174/1568009621666210127092828
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA Modifications and RNA-modifying Proteins in Cancer Therapy and Drug Resistance

Abstract: : The advent of new genome-wide sequencing technologies has uncovered abnormal RNA modifications and RNA editing in a variety of human cancers. The discovery of reversible RNA N6-methyladenosine (RNA: m6A) by fat mass and obesity-associated protein (FTO) demethylase has led to exponential publications on the pathophysiological functions of m6A and its corresponding RNA modifying proteins (RMPs) in the past decade. Some excellent reviews have summarized the recent progress in this field [1-11]. Compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 386 publications
0
22
0
Order By: Relevance
“…175 Further exploration of the role of m 5 C modifications in immune responses will provide a broader prospect for tumor immunotherapy 176 and tumor drug resistance. 177 There have been several companies targeting RNA apparent modifications. 178 The investigation of small-molecule inhibitors that are capable of targeting m 5 C modification-related effector proteins in the context of disease treatment may be a promising research direction.…”
Section: Clinical Relevance and Future Directionsmentioning
confidence: 99%
“…175 Further exploration of the role of m 5 C modifications in immune responses will provide a broader prospect for tumor immunotherapy 176 and tumor drug resistance. 177 There have been several companies targeting RNA apparent modifications. 178 The investigation of small-molecule inhibitors that are capable of targeting m 5 C modification-related effector proteins in the context of disease treatment may be a promising research direction.…”
Section: Clinical Relevance and Future Directionsmentioning
confidence: 99%
“…This may provide a potential strategy to develop coronavirus vaccines and antiviral drugs [328]. Recent studies have demonstrated that RNA modifications and RMPs play a critical role in controlling cancer cell proliferation, metastasis, immune evasion and drug resistance [329][330][331]. m 6 A and its RMPs have a bi-faceted role, i.e., acting as either an oncogene or a tumor suppressor in the pathogenesis of solid tumors and leukemia.…”
Section: Cap Nm and Cmtrmentioning
confidence: 99%
“…7.4.4. m 5 C and Its RMPs in Cancer RNA:m 5 C is mediated by NSUN RNA methyltransferase family proteins (Figure 2B) [51]. Upregulation of RNA:m 5 C and its writer proteins, especially NSUN1 and NSUN2, has been reported in a variety of solid tumors and leukemia and contributes to tumor cell proliferation, metastasis and drug resistance [55,57,331]. However, compared to a large body of studies on the pathophysiological function of m 6 A and its RMPs, much less is known about m 5 C and its RMPs.…”
Section: Rna Editing and Its Rmps In Cancermentioning
confidence: 99%
“… 5 Recent studies revealed that misregulated RNA modifications often result in aberrant gene expression and are closely related to the developmental diseases and cancers. 6 , 7 , 8 Different RNA species contain posttranscriptional modifications, and the diverse modifications on RNAs play essential functions in RNA metabolism, gene expression regulation and human diseases, including cancers. 9 , 10 Therefore, investigation of modifications on RNAs in the regulation of HCC progression could potentially identify regulatory factors and therapeutic targets in HCC.…”
Section: Introductionmentioning
confidence: 99%